MAQASYID ASY- SYARI’AH SEBAGAI METODOLOGI PENAFSIRAN AL-QUR’AN ALTERNATIF “ALA” JARINGAN ISLAM LIBERAL - M. Nurdin Zuhdi (AN NUR: Jurnal Studi Islam, 2012)
Liberal Islam Network (JIL) is one of the Islamic movement is quite controversial. Appears and the development of liberal Islamic Network has been warmly welcomed, but on the other hand also a lot of cursing. Liberal Islam Network movement is quite different from other Islamic movements. Inside the Liberal Islam Network special is a different view of Islam. Especially their concept of the importance of renewal in the methodology of interpretation of the Koran. How was the view of the Liberal Islam Network against al-Quran and its interpretation? Methodologies such as whether he offers as an alternative rule in interpreting the Koran? Liberal Islam Network believes that the Koran must be understood according to the context and spirit of the era. To understand the Qur'an that are suited to the context and spirit of his day is not enough just by using existing methodologies (classical methodology). This is where the Liberal Islam Network offers a methodology offers an alternative interpretation of the Koran based on Usul Fiqh (maqashid al-syari'ah or hermeneutics).